19-9 Pemberton Square, ca. 1885 - J. W. Black & Co. (Tufts Archival Research Center, 2005)
Street-level view northwest of (left to right) 19-9 Pemberton Square, located along the west side of Pemberton Square. The facades of the houses face east. Horse-drawn wagons and wooden barrels fill Pemberton Square. A street light is included in the lower-left corner of the photograph. A small grouping of trees located in the center of Pemberton Square is visible in the lower-right corner of the photograph. 4 5/8 x 7 3/4, 5 1/4 x 8 1/2 overall Cabinet photographs